Invisible Students: An Exploration of Refugee Students' Experiences at a Higher Education Institution - Kenney, Mia Amanda (Department of Sociology, 2023)
This study explores refugee students' experiences at the University of Cape Town (UCT). The study aims to provide an understanding of the challenges faced by this group of students, focusing on their experiences of refugee identity and institutional culture, in order to explore ways of adequately supporting refugee students within higher education institutions. The study utilises an exploratory single case study and a qualitative research design based on in-depth interviews with UCT refugee students, supplemented by institutional document analysis. The data was analysed using the conceptual framework of refugee identity, institutional culture, and the challenges refugees face within higher education. The study found that refugee students at UCT experience a sense of invisibility and precariousness within the institution. The study argues that refugee students are not fully acknowledged by the institution. This sense of invisibility influences their experience of the practical, academic, financial, and social support that the students receive. In addition, the study argues that refugee students are challenged by a forced upon refugee identity and label which has resultant emotional effects on the individuals' sense of self. The refugee label highlights a fragile and dichotomous state of being both invisible within a higher education institution and for some desiring to remain invisible given the negative connotations associated with the label. In order for refugee students to be adequately supported within a university, this study found and proposes that differentiated treatment, such as a team dedicated to supporting refugee students instead of a one-size-fits-all approach, is key for supporting the needs and requirements of refugee students.